Application of magnesium alloy sacrificial anode for restraining chloride ingress into mortar. (15th August 2022) - Wu, You; Xu, Jinxia; Gong, Wenjie; Wang, Fei
Highlights: Chloride ingress into mortar was restrained by Mg alloy sacrificial anode system. Output electrochemical parameters of Mg alloy anode in mortars were detected. Chloride profiles and electrochemical performance of steel in mortars were measured. Visual inspection of steel surface after immersion was performed. Abstract: This study aims to restrain the chloride ingress into mortar by magnesium alloy sacrificial anode system. Cube reinforced mortar specimens with embedded magnesium alloy anode meshes were prepared. The output electrochemical parameters of magnesium alloy mesh, the chloride profiles and corrosion electrochemical performance of steel in mortars immersed in chloride-contaminated solutions were detected. Besides, the visual inspection of steel surface after immersion was performed. The results indicate that the magnesium alloy mesh can restrain effectively chloride ingress into mortar. With increasing water-cement ratio and chloride content, the galvanic potential and current density between the steel and magnesium alloy mesh increase. The chloride diffusion coefficient of mortar decreases after the application of magnesium alloy sacrificial anode and the decreased magnitude rises with increasing water-cement ratio, chloride concentration and decreasing steel cover thickness. The mitigation of steel corrosion and morphology of the steel surface after immersion further demonstrate the good effect of magnesium alloy sacrificial anode on reducing chloride ingress into mortar.